Brief research report: Transcriptional blockade of angiotensin converting enzyme 2 modelled in human retinal pigment epithelial cells - Ashander, Liam M.; Lumsden, Amanda L.; Ma, Yuefang; Tan, Alwin Chun Rong; Appukuttan, Binoy; Daniel, Santhosh; Michael, Michael Z.; Smith, Justine R. (Frontiers in Drug Discovery, 2024)
As a key host protein involved in cellular infection by the severe acute respiratory syndrome coronavirus (SARS-CoV-2), angiotensin converting enzyme (ACE)2 is an ideal target for antiviral drugs. Manipulation of transcription provides opportunity for graduated blockade that preserves physiological functions. We sought to develop a model system for evaluating manipulation of ACE2 gene transcription using human retinal pigment epithelium. Retinal pigment epithelial cell isolates were prepared from human posterior eyecups (n = 11 individual isolates). The cells expressed ACE2 transcript and protein, and expression was not induced by hypoxia mimetic dimethyloxaloylglycine, or inflammatory cytokine IL-1β. ACE2 gene transcription factors were predicted in silico and cross-referenced with the human retinal pigment epithelial cell transcriptome, and five candidate transcription factors were identified: ETS proto-oncogene 1 transcription factor (ETS1), nuclear factor I C (NFIC), nuclear receptor subfamily 2 group C member 1 (NR2C1), TEA domain transcription factor 1 (TEAD1), and zinc finger protein 384 (ZNF384). The candidates were individually targeted in cells by transfection with small interfering (si)RNA. Knockdowns reduced mean cellular expression of all the transcription factors in comparison to expression in cells transfected with control non-targeted siRNA. Mean cellular ACE2 transcript was reduced under the condition of NR2C1 knockdown, but not for ETS1, NFIC, TEAD1, and ZNF384 knockdowns. Our findings build on previous work demonstrating the potential for drugging gene transcription. Importantly, we show the value of human retinal pigment epithelium as a system for evaluating ACE2 transcriptional blockade, a possible approach for treating SARS-CoV-2 infection. Brief Research Report.